Group membership, geography and shared ancestry: Genetic variation in the Basotho of Lesotho. Issue 1 (18th January 2016) - Montinaro, Francesco; Davies, Joseph; Capelli, Cristian
ABSTRACT: Objectives: The investigation of the evolution of cultural and genetic traits and how they interact represents a vibrant area of research in evolutionary genetics, whose dynamics are particularly relevant for our species. One of the key assumptions of the "gene–culture coevolution" framework is the coinheritance of cultural and genetic traits. A corollary of the model is that culturally defined groups with a unique (or a limited number of) common origin(s) whose membership is inherited only through the male or female line are expected to show a relatively low intragroup variation for genetic markers similarly transmitted. Across human societies this is expected to be the case for cultural toponymies and family names within patrilineal and matrilineal groups considered in association with the nonrecombining region of the Y chromosome (NRY) and the mitochondrial DNA (mtDNA) portion of the genome, respectively. This study aims at exploring the degree of correlation between culture and genetics by investigating the genetic variation of culturally and geographically defined groups. Methods: We analyzed the genetic variation at NRY and mtDNA in 181 individuals from the Basotho, a Southern African patrilineal population from Lesotho, in combination with information about group membership and geographic origin. Results: Our results show that (a) the genetic distance between individuals belonging to the same culturally defined group is lower than the population as a whole when NRY markers are considered; (b) cultural traits have a bigger impact than geography for the within‐group variation of Y chromosome, but not mtDNA; and (c) within‐group genetic variation is compatible with a more homogeneous origin for less common groups. Conclusions: Our results provided additional evidence for the relevance of the dual inheritance model (culture and genetics) in understanding the patterns of human genetic variation, as implied by gene–culture coevolution theory. Am J Phys Anthropol 160:156–161, 2016. © 2016 Wiley Periodicals, Inc.